Fund manager allocation - Jieyan Fang; Alexander Kempf; Monika Trapp (University of Cologne, Centre for Financial Research (CFR), 2012)
We show that fund families allocate their fund managers to different market segments such that their skill is rewarded best. Whether a fund manager's skill is rewarded by higher alpha depends on the efficiency of the market segment in which she works. Even skilled managers can generate alpha only if the market segment is inefficient. Fund families take this relation between skill and inefficiency into account and allocate their best managers to the least efficient market segment. They use this rationale when assigning newly hired fund managers as well as when reassigning managers they already employ. Depending on the manager's tenure, fund families use different signals for skill. For young managers, fund families rely mainly on the manager's general ability and education as measured by GMAT. For more experienced managers, they rely mainly on the manager's track record which reflects overall investment skill.
Keywords: 330; manager allocation; performance; skill; market efficiency